Role of Etv2‐positive cells in the remodeling morphogenesis during vascular development. (24th June 2013) - Kobayashi, Kumiko; Ding, Guo; Nishikawa, Shin‐Ichi; Kataoka, Hiroshi
Abstract : Etv2 is a critical determinant for the commitment of endothelial (EC) and hematopoietic (HPC) cells from mesoderm. Etv2 is assumed to be transiently required for EC commitment but dispensable after most ECs differentiate around E9.5. To confirm the time window of Etv2 requirement, Etv2 was ablated at different time points using ROSA26CreER mice. Unexpectedly, Etv2 ablation at E9.5 caused vascular remodeling defects in cranial and yolk sac vasculature. Immunostaining showed that Etv2+/VE‐cadherin (VECAD)− cells were present around forming vasculature, mostly co‐expressing Flk‐1 with a small number of Etv2+/VECAD+ cells, indicating that Etv2+/Flk‐1+/VECAD− cells are the major Etv2+ population promoting vascular remodeling around E9.5. Gene expression analysis showed up‐regulation of Fgf proteins, Il‐6, Glypican‐3 and matrix metalloproteases in Etv2+/VEDAC− cells over Etv2−/VECAD+ mature ECs. Blockade of those factors caused reduced EC sprouting in ex vivo explant culture from E9.5 embryos, suggesting the functional significance of environmental factors derived from Etv2+ cells. Altogether, we propose that Etv2+/VEDAC− cells around E9.5‐E10.5 provide extracellular factors to complete vascular morphogenesis in addition to becoming differentiated ECs incorporated into vessels. This insight for the new role of Ets protein in perivascular Flk‐1+/VECAD−/(Etv2+) cells to induce expression of angiogenic factors may provide another strategy to control angiogenesis.